Fatigue cumulative damage and crack propagation analysis of welded joints - Shi, Zhao Feng. (2009)
Fatigue analysis of welded joints for low and medium carbon steels is well established and documented in British Standard, BS 7608. However, this current fatigue design code does not cover high strength steel structures, particularly, weldments of armor steel plates with austenitic stainless steel weid metal. Due to the high mismatch between the weid metal and parent metal properties, the fatigue behavior of such welded joints needs to be examined before a fatigue design procedure can be developed. Furthermore, fatigue crack initiation is the least understood part in the fatigue assessment of weldments and further study is reported in this thesis.